A flicker in the dark [large type] - Willingham, Stacy (Wheeler Publishing/Thorndike Press, a part of Gale, a Cengage Company, 2022)
"When Chloe Davis was twelve, six teenage girls went missing in her small Louisiana town. By the end of the summer, her own father had confessed to the crimes and was put away for life, leaving Chloe and the rest of her family to grapple with the truth and try to move forward while dealing with the aftermath. Now twenty years later, Chloe is a psychologist in Baton Rouge and getting ready for her wedding. When a local teenage girl goes missing, and then another, that terrifying summer comes crashing back. Is she paranoid, seeing parallels from her past that aren't actually there, or for the second time in her life, is Chloe about to unmask a killer?"-- Back cover.